2000
DOI: 10.1046/j.1365-2923.2000.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

A review of the evaluation of clinical teaching: new perspectives and challenges *

Abstract: Using this model of evaluation, a connection can be made between teaching and learning about all the expected roles of a physician. This can form the basis for systematic investigation into the relationship between the quality of teaching and the desired outcomes, the improvement of student learning and the achievement of better health care practice. It is suggested that the extent of effort and resources devoted to evaluation should be commensurate with the value assigned to the evaluation process and its out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0
8

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(114 citation statements)
references
References 31 publications
3
102
0
8
Order By: Relevance
“…They can be used for performance appraisal and promotion up the academic ladder (Cashin 1999;Berk 2005;Ramani 2006), but also to improve teaching practice (Snell et al 2000). In a review study, Marsh and Roche found evidence of the usefulness of students' evaluations in improving teaching effectiveness, provided the utilised instruments were thoroughly validated (Marsh & Roche 1997).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be used for performance appraisal and promotion up the academic ladder (Cashin 1999;Berk 2005;Ramani 2006), but also to improve teaching practice (Snell et al 2000). In a review study, Marsh and Roche found evidence of the usefulness of students' evaluations in improving teaching effectiveness, provided the utilised instruments were thoroughly validated (Marsh & Roche 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Most authors of these recent publications agree that performance evaluations can not only help teachers to identify areas for improvement (Snell et al 2000;Morrison 2003), but also stimulate them to reflect on their teaching practice and plan concrete actions for improvement as part of a faculty development programme (Seldin 2006;Arreola 2007). Many of them have endorsed the importance of reflection for enhancing professional growth (Hatton & Smith 1995;Ward & McCotter 2004;Korthagen & Vasalos 2005;Tigelaar et al 2006;Watts & Lawson 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Nous avons donc besoin que les enseignants reconnaissent la valeur des formations et les recommandent à leurs collègues. Nous renvoyons le lecteur aux travaux de Goldie [153] pour une description des diffé-rents outils d'évaluation des programmes de formation et à ceux de Snell et al [154] pour une discussion sur les principes relatifs à l'évaluation des formations cliniques.…”
Section: éValuer L'efficacité Du Programme Et Donner Du Feed-backunclassified
“…They can be supported to do so effectively by evaluating clinical teaching and providing them with feedback on their clinical teaching performance (Snell et al 2000). In this process, four steps are understood to be involved: (1) assessing the performance, (2) providing assessment feedback, (3) reflection and decision-making and (4) using feedback for learning and change (Sargeant et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of assessment instruments is available, the most prevalent one being the completion of a standardized teacher-rating form by learners (Snell et al 2000;Beckman et al 2003;Fluit et al 2010). In choosing a questionnaire, it is essential that it is valid, reflects relevant teacher tasks, and is based on theory of learning.…”
Section: Introductionmentioning
confidence: 99%